Sistem Pengelolaan Lena Oleh Laundry Section Di Hotel Copthorne Orchid Penang Malaysia - Poppy Arnold Kadir; Krishna Anugrah; Rita Andrayana Sari (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2020)
This study aimed at revitalizing the management system of lena by laundry section in hotel Copthorne Orchid Penang to fulfill the Operational Standard Procedure. This research applied qualitative method which provided data description of written and spoken from the respondent by using observation, interview, and documentation.The research result showed that lena management system by laundry section in hotel of Copthorne Orchid Penang did not fulfill the operational standard procedure because the officers did not follow the procedure and there was no facility of laundry in the hotel which was caused the outside laundry played the role of lena management, in consequence it distrubed the operational of the hotel. As a result, it is a major concern to the hotel to provide the laundry facility and gain the employee to maximize the lena management system by laundry section in Hotel Copthorne Orchid Penang.